Time-restricted feeding and cognitive function in sedentary and physically active elderly individuals: Ramadan diurnal intermittent fasting as a model - Boujelbane, Mohamed Ali; Trabelsi, Khaled; Jahrami, Haitham A.; Masmoudi, Liwa; Ammar, Achraf; Khacharem, Aïmen; Boukhris, Omar; Puce, Luca; Garbarino, Sergio; Scoditti, Egeria; Khanfir, Saber; Msaad, Aymen; et al. (Frontiers in Nutrition, 2022)
Objectives: This study aimed to investigate the effects of RIF on cognitive performance, sleep quality, daytime sleepiness, and insomnia in physically active and sedentary elderly individuals. Methods: A total of 58 participants (62.93±3.99 yrs) were assigned to one of the following two groups: a sedentary group (control group) fasting during Ramadan (n=32) and a physically active group (n=26) who continued to train while fasting during Ramadan. Participants were assessed two weeks before Ramadan and during the fourth week of Ramadan. On each occasion, participants completed a digital assessment of their cognitive performance. Further, to assess sleep parameters, participants responded to the Pittsburgh sleep quality index (PSQI), insomnia severity index (ISI) and the Epworth sleepiness scale (ESS) questionnaires. Results: Compared to before Ramadan, performance in executive function (p= 0.035), attention (p= 0.005), inhibition (p= 0.02), associative memory (p= 0.041), and recognition memory (p= 0.025) increased significantly during Ramadan in the physically active group. For the sedentary group, associative learning performance decreased (p= 0.041), whilst performances in the remaining domains remained unchanged during Ramadan. Global PSQI, ISI, and ESS scores indicated that both groups suffered from poor sleep quality and excessive daytime sleepiness, with significantly higher negative effects of RIF observed in the sedentary group. Conclusion: Older adults who continue to train at least three times/week during Ramadan may improve their cognitive performance despite the impairment of sleep quality.